EXPERIENCE IN CREATING A PROBATION SYSTEM FOR CONVICTS ON THE EXAMPLE OF FRANCE, KAZAKHSTAN AND THE KYRGYZ REPUBLIC - ZVONOVA A.V. (Legal Bulletin)
The modern penitentiary policy of most states is aimed at the process of humanizing the execution of criminal punishment. In this regard, the institution of execution of punishments is rapidly developing. without isolation from society, creating and modernization of the probation service. The relevance. The main goal. The creation of a probation service will reduce the level of recidivism, solve the problem of overcrowding in penitentiary institutions, and also contribute to a more effective implementation of the rights and legitimate interests of those sentenced to criminal punishment. The methodological basis of the scientific article is the method of materialistic dialectics, general scientific and private scientific methods, taking into account the principles, techniques and methods inherent in the domestic penitentiary science. In particular, the author used compara-tive-legal, logical-legal, sociological and others.